If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3) + y = 11 Multiply 4 * 3 12 + y = 11 Solving 12 + y = 11 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + y = 11 + -12 Combine like terms: 12 + -12 = 0 0 + y = 11 + -12 y = 11 + -12 Combine like terms: 11 + -12 = -1 y = -1 Simplifying y = -1
| 4x-7y=11fory | | 5.9q-2.2-5.3q=-0.4q-4.3 | | 42n^3+6n^2=0 | | 2(-2)-3x=5 | | 5x^2-5x^2= | | N^2-8n=-15 | | 2x^2-21x=11 | | 12x^2+51x+45= | | N^2-8k-3=-3-5k^2 | | x/5+x/7=6/5 | | x^2+16=36+x^2+4 | | -15p^2+17p+4= | | 2(5x+5)-3= | | 3p+4m-6-p+3m+5p-11-m= | | 2x+5(3/2)=16 | | 8x^2-16x-280= | | 2x^2+12x=3x-9 | | 1/x=0.01 | | 126=(x+2)(2x) | | 6n^2+9+12n-6-24=0 | | 2(-3)+5(x)=16 | | y-20n=6y | | 2a+8=2 | | 2(x+3)+4=20 | | (8x+25)*8/8 | | n=2m+3 | | s-21=-49 | | (24x^2+18x)/(24x) | | y^2+6y-4x+25=0 | | 4m+5n=57 | | x^2+7x-8=-14 | | 4(3x+8)-4=19 |